Expanding the TDP-43 Proteinopathy Pathway From Neurons to Muscle: Physiological and Pathophysiological Functions - Versluys, Lauren; Ervilha Pereira, Pedro; Schuermans, Nika; De Paepe, Boel; De Bleecker, Jan L.; Bogaert, Elke; Dermaut, Bart (Frontiers in Neuroscience, 2022)
TAR DNA-binding protein 43, mostly referred to as TDP-43 (encoded by the TARDBP gene) is strongly linked to the pathogenesis of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). From the identification of TDP-43 positive aggregates in the brains and spinal cords of ALS/FTD patients, to a genetic link between TARBDP mutations and the development of TDP-43 pathology in ALS, there is strong evidence indicating that TDP-43 plays a pivotal role in the process of neuronal degeneration. What this role is, however, remains to be determined with evidence ranging from gain of toxic properties through the formation of cytotoxic aggregates, to an inability to perform its normal functions due to nuclear depletion. To add to an already complex subject, recent studies highlight a role for TDP-43 in muscle physiology and disease. We here review the biophysical, biochemical, cellular and tissue-specific properties of TDP-43 in the context of neurodegeneration and have a look at the nascent stream of evidence that positions TDP-43 in a myogenic context. By integrating the neurogenic and myogenic pathological roles of TDP-43 we provide a more comprehensive and encompassing view of the role and mechanisms associated with TDP-43 across the various cell types of the motor system, all the way from brain to limbs.